A Preventable Maternal Death Case Report in Haho Health District, Togo, 2018 (Archives of Clinical and Medical Case Reports, 2019)
From 1990 to 2015, maternal mortality has decline by 43.9 per cent worldwide. In sub-Saharan Africa countries including Togo, it’s still a great concern. Sustainable Development Goals recommend to achieve a maternal mortality ratio of less than 70 maternal deaths per 100,000 live births by 2030. We report a case of maternal death of a Christian pregnant woman that occurred in Haho health district in 2018. Data were collected through a review of registers, medical and antenatal records and verbal autopsy. The deceased suffered of severe pre-eclampsia like during her two previous pregnancies that ended with two stillbirths, but this time around she could not survive it despite the six antenatal visits with a gynaeco-obstetrician. Actually, she had the strong believe that the two stillbirths was uncommon and a result of a spell cast on her, and that only her faith through prayers could deliver her. Therefore, she did not comply with her reference to a hospital with a surgical service for a cesarean delivery. Her death was preventable. There is a need to strengthen patients’ therapeutic education and communication around diseases especially during pregnancies in order to help them know what faith cannot help achieve.